Development of a bleeding scale and hemostasis algorithm in cranial neurosurgery - Eyüpoglu, Ilker Yasin; Tuettenberg, Jochen; Schebesch, Karl Michael; Buhl, Ralf; Hampl, Jürgen A.; Kiriyanthan, George D.; Scheiwe, Christian (Heliyon, 2023)
Effective hemostasis is crucial in neurosurgery as anatomical and functional considerations reduce tolerance for any bleeding. The classification of bleeding severities is a necessary step to enable neurosurgeons to counteract bleeding during surgery. Even though bleeding scales are used for a variety of surgical specialties, they cannot be transferred to cranial neurosurgery without adaption, and no consensus on the nature of such a classification exists to date. Moreover, there is plethora of topical hemostasis products with diverse mechanisms of action and application available. Clinical studies investigating those products used in neurosurgery did not define standardized procedures. This article demonstrates the systematic establishment of both a bleeding scale and a hemostasis algorithm to close this gap in the assessment of intracranial bleeding. The expert panel consisting of 7 members from different neurosurgical centers developed a qualitative bleeding scale with the peculiarities of neurosurgical procedures, based on the experience of each member in daily practice. The hemostasis algorithm is a recommendation for neurosurgeons to aid in the decision-making process to control any sort of bleeding, taking into account the rational use of available hemostatics, depending on type and location of bleeding, as well as the mechanism of action of such agents. Effectiveness of hemostasis, surgery times and economic costs can be optimized by applying the algorithm in daily practice.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Bleeding scale; Bleeding score; Hemostasis; Hemostasis algorithm; Intracranial bleeding; Topical hemostats